On the Alkalinity of Solid Catalysts for Transesterification of Dimethyl Carbonate and Ethanol - Tianyu Zhang; Shun Wu; Weihua Shen; Yunjin Fang (Applied Sciences)
In this study, Mg-Al-Zn, MgO, Al2O3, and ZnO were synthesized via the co-precipitation method and evaluated as catalysts for the transesterification reaction of dimethyl carbonate (DMC) and ethanol. The crystal structure, morphological characteristics, pore structure properties, and alkaline properties of the catalysts were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) surface area analysis, temperature-programmed desorption of CO2 (CO2-TPD), and Fourier transform infrared spectroscopy (FTIR). The surface alkali strength and alkalinity of the solids were determined using the Hammett indicator method and non-aqueous titration. When Al2O3 and ZnO are used as catalysts for this transesterification, the conversion rate of dimethyl carbonate is relatively low. When MgO and Mg-Al-Zn are used as catalysts, the conversion rate of dimethyl carbonate is higher. This indicates that the alkali strength of the catalyst for the transesterification reaction needs to be greater than 9.3. Additionally, the activity of the catalysts is also related to the amount of the alkaline sites on the solid surface. The alkali strength of MgO is greater than 11; its excessively high alkali strength will react with CO2 and H2O during use, resulting in a reduction in the number of alkaline sites and thus showing unsatisfactory reactivity. The alkaline strength of the Mg-Al-Zn catalyst ranges from 9.3 to 11.0. When used for the first time, the number of alkaline sites decreases, and then the alkalinity remains at a certain value. Therefore, the alkaline strength of the solid catalyst for the transesterification reaction between DMC and ethanol needs to be between 9.3 and 11.0 so that the number of alkaline sites on the catalyst surface remains unchanged and the catalytic activity remains stable.